Resistant Hypertension and Obstructive Sleep Apnea in the Primary-Care Setting - M. Demede (International Journal of Hypertension, 2011)
We ascertained the prevalence of resistant hypertension (RH) among blacks and determined whether RH patients are at greater risk for obstructive sleep apnea (OSA) than hypertensives. Method. Data emanated from Metabolic Syndrome Outcome Study (MetSO), a study investigating metabolic syndrome among blacks in the primary-care setting. Sample of 200 patients (mean age = 63 ± 13 years; female = 61%) with a diagnosis of hypertension provided subjective and clinical data. RH was defined using the JNC 7and European Society guidelines. We assessed OSA risk using the Apnea Risk Evaluation System ARES), defining high risk as a total ARES score ≥6. Results. Overall, 26% met criteria for RH and 40% were at high OSA risk. Logistic regression analysis, adjusting for effects of age, gender, and medical co morbidities, showed that patients with RH were nearly 2.5 times more likely to be at high OSA risk, relative to those with hypertension (OR = 2.46, 95% CI: 1.03–5.88, P<.05). Conclusion. Our findings show that the prevalence of RH among blacks fell within the range of RH for the general hypertensive population (3–29%). However, patients with RH were at significantly greater risk of OSA compared to patients with hypertension.